Choledochal cysts: Management and long-term follow-up. Issue 4 (August 2021) - Serin, Kursat Rahmi; Ercan, Leman Damla; Ibis, Cem; Ozden, Ilgin; Tekant, Yaman
Abstract: Background: Choledochal cysts are congenital anomalies that can occur at any level of the biliary tree. They carry long-term risk of biliary complications and cancer development. Complete excision of all involved bile ducts is recommended. Methods: Patients treated between 1995 and 2019 were reviewed retrospectively. Results: Sixty patients; 46 female and 14 male with a median age of 41 years (range 13–83) were included in the study. Mild abdominal pain was the most common presenting symptom (60%). Majority of the patients had Todani type I cysts (67%). Concomitant biliary malignancy was diagnosed in five patients (9%). Eight patients were followed-up conservatively (13%). Twenty-five patients were treated by excision of the extrahepatic bile ducts and Roux-en-Y hepaticojejunostomy, liver resection was added in seven, pancreatoduodenectomy was done in three and liver transplantation in one. There was no perioperative mortality. Postoperative complications developed in 17 patients (34%), two requiring surgical treatment. Four of the five patients with malignancies died at a median 42 months (range 6–95) following surgery. Median 62 months (range 8–280) follow-up was available in 45 surgically treated patients, 19 followed-up for more than 10 years. None of the patients developed malignancy during follow-up. Four patients (17%) were readmitted for anastomotic strictures requiring treatment. Conclusion: The majority of choledochal cysts are Todani type-I and early cyst excision is the mainstay of management, which may decrease the risk of malignant transformation. Highlights: Surgery for choledochal cysts is recommended because of the cholangiocarcinoma risk. Surgery is controversial for patients with intrahepatic extension. A wide range of surgical treatment from CBD resection to LTx may be required. Asymp patients who diagnosed elderly needs clarified whether treatment is needed.